Durability of Bungur wood (Lagerstroemia speciosa Pers.) results of smoking against marine borer attacks - Riana Anggraini; Jauhar Khabibi; Wahyudi Wahyudi (Kementerian Perindustrian, 2022)
Bungur wood (Lagerstroemia speciosa Pers.) is often used as a construction over ocean waters and is still widely available. Based on (SNI) 01-7210-2006 concerning types of wood for shipbuilding, bungur wood is included in the construction materials for traditional wooden ships, such as: frames, ivory, titles, leather and gladak boards. Bungur wood has low resistance to wood destroying organisms (III-IV), but has a fairly strong resistance to waves and strong winds (I-II). Application of fumigation on wood has long been done to preserve wood. The purpose of the research was to analyze the interaction between smoking duration and the depth of treated wood feed to the marine borer attack. The treatment factors used were the length of smoking time (control (without smoking) 6 hours, 12 hours and 24 hours) and the depth of feeding (two meters and four meters. The tests observed were weight gain after smoking, intensity of marine borer attack and identification of marine borer. After feeding for 6 months the results showed the interaction of smoking duration and feeding depth of bungur (Lagerstroemia speciosa Pers.) significantly affected in reducing the intensity of marine borer attack. The best thing is that smoking for 12 hours at two meters of feed can increase the durability of bungur wood to Durability class II from the intensity of marine borer attack